HUBUNGAN PENGETAHUAN PERAWAT TENTANG PEMBERIAN LABEL TRIASE DENGAN TINDAKAN PERAWAT BERDASARKAN LABEL TRIASE DI UGD RS KEBONJATI BANDUNG - Stevani Basry; Siti Rahayu; Andi sukandi (LPPM Akper Kebonjati, 2023)
The triage system is one of the implementations of the risk management system in the Emergency Department so that patients who come receive treatment quickly and appropriately according to their needs using available resources. The knowledge, attitudes and skills of emergency room nurses are very much needed in making clinical decisions so that errors do not occur in making triage selections so that patient treatment can be more optimal and focused. The aim of this study was to analyze the relationship between nurses' knowledge about giving triage labels and nurses' actions based on triage labels in the emergency room at Kebonjati Hospital, Bandung. This study used a correlative descriptive design, namely to determine the relationship between nurses' knowledge about giving triage labels and nurses' actions based on triage labels in the emergency room at Kebonjati Hospital, Bandung. The total population sample technique was 12 emergency room nurses at Kebonjati Hospital, Bandung. Based on the results of research on respondents' knowledge, it was found that almost all respondents had good knowledge about triage labeling. The ages of the respondents in this study were mostly 20–25 years old, this influenced the respondents' level of knowledge.